Konseptualisasi citra hara 'perut' dalam idiom bahasa Jepang - Saifudin, Akhmad (Japanese Research on Linguistics, Literature, and Culture, 2018)
Hara simply means belly, but for Japanese people it means more than physical. Hara is a concept, an important concept related to Japanese human life. This paper discusses the conceptualization of hara image for Japanese people. The study utilizes 25 idioms that contain hara 'belly' word that are obtained from several dictionaries of Japanese idioms. This paper is firmly grounded in cognitive linguistics, which relates linguistic expressions to human cognitive experience. The tool for analysis employed in this paper is the “conceptual metaphor theory pioneered by Lakoff and Johnson. This theory considers human perception, parts of the body, and people's worldview as the basis for the structure of human language. The analysis of this paper results that metaphorically, hara 'belly' is an entity and a container, which contains important elements for humans, such as life, mind, feeling, mentality, and physical. The concept of hara 'belly' for Japanese people is to have a spiritual, psychological, social and cultural, biological, and physical image.Keywords: conceptualization, conceptual metaphor, hara, belly, idioms, image